Deep brain stimulation as a possible treatment of hyperthermia in patients with serotonin syndrome. (June 2020) - Koleva, K.; Pavlov, O.; Nikolov, R.; Behr, R.
Abstract: Maintaining a body temperature within a narrow range is vital for the survival of all mammals, including humans. With the help of optogenetics, a better understanding of the thermoregulatory organs and pathways is achieved. Optogenetic activation of the GABAergic neurons in the ventral part of the lateral preoptic nucleus (VLPO) leads to decrease in the body temperature. On the other hand, number of drugs could alter the thermoregulatory balance, leading to a hyperthermic state, such as serotonin syndrome (SS). SS is a potentially life-threatening clinical condition that occurs as a result of a drug-induced increase in the intrasynaptic serotonin (5-hydroxytryptamine, 5-HT) levels due to overdose of a single drug or due to interaction between two or more drugs with serotonergic mechanism of action. In this hypothesis, we propose a novel method for the treatment of hyperthermia, a core clinical sign of serotonin syndrome, through deep brain stimulation (DBS). An electrode is stereotactically placed in the VLPO, which may lead to reduction of the core body temperature. If proven effective, this technique should be left as a salvage method for reduction of hyperthermia, where the drug treatment is insufficient or ineffective. This technique could be used for the treatment of other syndromes, where hyperthermia takes a central place, including malignant hyperthermia, neuroleptic malignant syndrome, etc. DBS, on the other hand, could be used alone to induce hyperthermia in patients with malignant diseases. Hyperthermia improves the immune response, improves the drug penetration and stop the repair of already damaged tumor cells after chemotherapy or radiotherapy.